Guadua angustifolia biochar/TiO2 composite and biochar as bio-based materials with environmental and agricultural application - Luis A. Cañon-Tafur; Juan F. Mateus-Maldonado; Hair Santiago Lozano-Puentes; Carlos D. Herrera-Acosta; Juan J. Sánchez-Matiz; Lucía A. Díaz-Ariza; Geison Modesti Costa; Luis C. Jiménez-Borrego; Ana K. Carrascal-Camacho; Aura M. Pedroza-Rodríguez (Scientific Reports)
Abstract Globally, the companies that make commercial use of bamboo culms produce different kinds of solid waste rich in lignocellulosic biomass, which in some cases is not used and is discarded in landfills or incinerated in the open air; losing the possibility of recovering them and using them in other productive sectors. The research objective were to produce a biochar from Guadua agustifolia  Kunth sawdust, evaluate its potential environmental and agricultural use, obtain a biochar/TiO2  composite to inactivate Escherichia coli and use the biochar as a soil conditioner in medicinal plants producing phenolic compounds and flavonoids. Biochar composite (produced at 300 °C for 1 h) involved TiO2 at 450 °C for 1 h for inactivation of E. coli (initial concentration: 6.5 ± 0.3 Log10 CFU mL− 1). For agriculture, 2% biochar was used to evaluate B. pilosa L. and G. angustifolia  plant growth for 90 days. The biochar/TiO2  composite had a high photocatalytic activity on E. coli, generating a final count of 1.97 ± 0.2 Log10 CFU mL− 1 after 60 min. Biochar (2%) increased the total phenol and flavonoid content in the medicinal plant B. pilosa L. and total phenols in G. angustifolia, tested at the nursery stage. This study provides new information on the conversion and use of G. angustifolia sawdust as an alternative for new bio-based materials with environmental and agricultural applications. In addition, obtaining biochar and composite could positively impact the bamboo production chain in Colombia because of renewable and globally accepted alternatives that help capture gaseous emissions causing the greenhouse effect.